Annual Plan 1978-79 and Review of Plan Performance 1977-78 - Planning Commission (Planning Commission, 1977)
As in previous years this Annual Plan survey presents a review of Plan performance for 1977-78 together with the salient features of the current year’s Plan. Since complete information about financial outlays on schemes in the State and Central Plans and achievements in physical terms in key sectors of the economy becomes available only 3 to 6 months after the end of any financial year, it has not been possible to present this survey earlier. Clearly it would be desirable that the Annual Plan for any year should be available to Parliament and to the public at the beginning of the year. From next year (1979-80) the Planning Commission proposes to replace the Annual Plan survey with two documents viz.
Government of India Planning Commission
Government of India Planning Commission